Analisis Faktor-Faktor yang Mempengaruhi Kinerja Pegawai di Subbag Rumah Tangga Biro Umum dan Keuangan Universitas Negeri Malang - Hidayatunnafiq, Faul (Jurnal Ilmiah Administrasi Publik, 2021)
Employee performance has an important role in supporting the success and success of the organization. The background of this research is the low performance of the teaching staff in the Household Subdivision of the State University of Malang (UM). Some indicators of performance decline include employee discipline at work, and ineffective performance of the UM Household Subdivision. The problem is thought to be related to factors that affect performance, for this reason it is necessary to analyze the factors that affect the performance of employees in the UM Household Subdivision. This study aims to analyze the effect of training, competence, leadership perception, compensation, experience, and motivation on performance both directly and through work motivation as a mediator variable. The results of this study indicate that training has a significant effect on performance, followed by compensation and leadership perceptions. Activities that are relevant to improving employee performance are further intensifying education and training programs, increasing compensation, and strengthening leadership management at UM.